Myositis-specific and myositis-associated autoantibodies in Saudi patients - Rim Sghiri; Zahid Shakoor; Mohammed Ahmed; Nuha Nasser Alrajhi; Adel Almogren (Wolters Kluwer Medknow Publications, 2024)
Background and Objectives: Data about myositis-specific autoantibodies (MSAs) and myositis-associated autoantibodies (MAAs) in Saudi patients are limited, and most studies have focused on anti-Jo1. This study aimed at reporting the MSAs and MAAs in Saudi population and their significance. Methods: This was a retrospective analysis of 190 Saudi patients investigated for idiopathic inflammatory myopathies (IIMs) between January 2019 and January 2023. Data for MSAs and MAAs were collected from medical records of patients. MSAs and MAAs were detected by line immunoblot. Results: Among the 190 sera tested, 47 yielded positive results for MSAs. There were 19 (40.4%) patients with IIMs, 20 (42.6%) with interstitial lung disease (ILD), and 8 (17%) with connective tissue diseases. Anti-signal recognition particle (SRP) was the most common MSA and was positive among 16 (34%) patients. Anti-PL-12 was the most frequent anti-synthetase antibody (21.3%) followed by anti-PL-7 (19.1%). Anti-Jo1 was associated with Raynaud's phenomenon (odds ratio [OR] = 9, 95% confidence interval [CI] = 1.3-60, P = 0.037) and with ILD (OR = 29, 95% CI = 2.4-351, P = 0.008) in patients with IIMs whereas anti-PL-7 was associated with ILD in the rest of the patients (OR = 6, 95% CI = 1.1-33, P = 0.021). MAAs were positive in 24 (51.1%) patients with anti-Ro52 as the most frequently detected antibody (29.8%). Conclusion: We confirm the association of MSAs with IIMs and ILD in the Saudi population. Anti-SRP and anti-PL-12 were the most common MSAs. These observations should be validated by large-scale studies.